The Effect of Strategic Vigilance in Achieving Sustainable Competitive Advantage: Analytical Research at Ashur International Bank - Edan Alkhazraje, Mohammed; Entisar Azeez Hussein; Mahmood Osama Abdulwahhab (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
This research aims to know the interest of Ashur International Bank management in the role played by strategic vigilance in achieving sustainable competitive advantage by providing decision-makers with proactive and important information about internal and external environmental variables, so the intellectual cover of the problem stems from the extent of the bank's management ability to achieve sustainable competitive advantage in light of the multiple markets of the Iraqi private commercial banks, as well as governmental banks. Hence the importance of the research lies in presenting the accumulation of knowledge for strategic vigilance, which is one of the modern approaches in the field of strategic management, while the sustainable competitive advantage is the most influential in the work of banks due to its connection with their future and their business. The sample consists of (125) individuals (department heads, division and unit officials, and employees) in the surveyed bank. A questionnaire was used to collect data and distributed to a sample of (60) individuals, from which (50) valid forms were retrieved for analysis. The most important conclusion was the bank's management focuses in its strategic thinking on the dimensions of strategic vigilance in different ways according to the vigilance sequence (commercial, environmental, technological, and finally competitive vigilance)